Evaluación de la disminución de tiempos de proceso y el correcto anclaje de las tintas offset con la incorporación de aditivos de secado en la empresa Cartonería Industrial S.A.S.- Inducarton (2017)
The present project is developed in order to solve the problems of drying and anchoring of the ink in the products printed on the sealed substrates in the company Cartonería Industrial S.A.S - Inducartón through of the incorporation of drying additives that help this one.